2019
DOI: 10.30654/mjgo.10017
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Prior Knowledge of The Abortion Law and Decision-Making on Choice of Place for Abortion Services in Accra, Ghana

Abstract: Background: Despite less restrictive abortion laws in Ghana than in other African Countries, women still resort to unsafe abortions. This study examines the cross-sectional relationship between women's prior knowledge of Ghana's abortion law and type of provider accessed in Accra, Ghana.Methods: Women seeking induced abortion (320) and those being treated for post-abortion complications (81) were sampled from four purposive selected health facilities (2 public and 2 private). Bivariate and multivariable binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
1
4
0
Order By: Relevance
“…Indeed, most people including some providers are not aware of the details of the legal status of induced abortion in Ghana and often exhibit attitudes that negatively affect access to safe abortion care in the country. 46,47 Similar observations have been made in India and Zambia where abortion is legal yet unsafe abortions still prevail due to misinformation about the law. 48 By policy, Ghana has gone far by ensuring that in giving consent for an induced abortion in Ghana the decision is predominantly a prerogative of the pregnant woman.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, most people including some providers are not aware of the details of the legal status of induced abortion in Ghana and often exhibit attitudes that negatively affect access to safe abortion care in the country. 46,47 Similar observations have been made in India and Zambia where abortion is legal yet unsafe abortions still prevail due to misinformation about the law. 48 By policy, Ghana has gone far by ensuring that in giving consent for an induced abortion in Ghana the decision is predominantly a prerogative of the pregnant woman.…”
Section: Discussionsupporting
confidence: 57%
“…21-25 Other studies also examine the association between women’s knowledge of abortion law and the practice of induced abortion. 26-29 Further, while some studies use hospital-based data in examining this phenomenon 27 30-32 and community-based surveys 26 28 33 34 , others use nationally representative surveys. 20 25 35 36 These previous studies did not fully explore and examine how demographic, socio-economic factors influence women’s knowledge on the legality of abortion under some conditions (rape, incest, risk to mothers and foetus health) and how that interaction determines their choice of abortion methods.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous studies in Ghana reported poor abortion law knowledge. This was reported in a study by Gbagbo, where only 33% of women knew abortion was legal in Ghana [28]. Similarly, a study by Reiger et al among young women and men in Accra, Ghana, revealed that poor knowledge among respondents was high [6].…”
Section: Plos Global Public Healthmentioning
confidence: 71%